Laboratory Assessment of Nyamplung Seeds (Calophyllum Inophyllum Linn) Base Cosmetic Products - Yusran Khery; Aliefman Hakim; Joni Rokhmat; AA Sukarso; Husnul Hatimah; Febriana Lidia Wati (Jurnal Penelitian Pendidikan IPA, 2024)
The development of the cosmetics industry in Indonesia is currently very rapid with average market growth reaching 9.67 % per year. The high market potential gives rise to tight business competition in the cosmetics industry, thus encouraging manufacturers to continue to innovate to create new product variations to meet society's demands for cosmetics as a complement to an attractive everyday appearance. This study aims to evaluate the physical characteristics of facial masks, body scrubs and sunscreens from Nyamplung (Calophyllum inophyllum) seed extract at various concentrations (5%, 10%, 15%). The test results showed that the three preparations met the standard physical property test parameters (organoleptic, pH, viscosity, spreadability, etc.). The facial mask formula with 10% extract was most liked by the panelists. Body scrub and sunscreen formulas with 10-15% extract also provide the best physical test results. The SPF value of sunscreen increases with increasing extract concentration up to the ultra category (SPF 17.42 at 15%). This study concludes that Nyamplung seed extract has the potential to be used as a natural ingredient for facial masks, body scrubs and sunscreen with an optimum concentration of 10-15%. Further research is needed regarding antioxidant activity and product stability testing. Overall, the three cosmetic preparations from Nyamplung seed extract show good prospects for development by paying attention to the best extract concentration of each product